Innate Lymphoid Cells in Autoimmune Diseases - Clottu, Aurelie S.; Humbel, Morgane; Fluder, Natalia; Karampetsou, Maria P.; Comte, Denis (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILC) are a heterogeneous group of immune cells characterized by lymphoid morphology and cytokine profile similar to T cells, but which do not express clonally distributed diverse antigen receptors. These particular cells express transcription factors and cytokines reflecting their similarities to T helper (Th) 1, Th2 and Th17 cells and are therefore referred to as ILC1, ILC2 and ILC3. Other members of the ILC subsets include lymphoid tissue inducer (LTi) and regulatory ILC (ILCreg). Natural killer (NK) cells share a common progenitor with ILC, and also exhibit a lymphoid phenotype without antigen specificity. ILC are found in low numbers in peripheral blood, but are much more abundant at barrier sites such as the skin, liver, airways, lymph nodes and the gastro-intestinal tract. They play an important role in innate immunity due to their capacity to respond rapidly to pathogens through the production of cytokines. Recent evidence has shown that ILC also play a key role in autoimmunity, as alterations in their number or function have been identified in systemic lupus erythematosus, systemic sclerosis and rheumatoid arthritis. Here, we review recent advances in the understanding of the role of ILC in the pathogenesis of autoimmune diseases, with particular emphasis on their role as a potential diagnostic biomarker and as therapeutic targets.